2017
DOI: 10.1108/jsocm-01-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of sports sponsorship for public health and social marketing

Abstract: Purpose This paper aims to provide a systematic review of evaluations of public health and social marketing campaigns reporting the use of sports sponsorship. Sports sponsorship is a key health promotion strategy, yet academic literature on the use of sponsorship in social marketing and public health is surprisingly limited. Design/methodology/approach Seventeen studies were identified following systematic literature review procedures. Findings Coupling of social marketing and public health sponsorship wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…Recent research has identified that healthy sponsorships have led to increased awareness of and preferences for healthy products while at the same time decreasing preferences for unhealthy products (38,39) . Furthermore, healthy sponsorships are likely to be mutually beneficial to business and sporting clubs (40) .…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has identified that healthy sponsorships have led to increased awareness of and preferences for healthy products while at the same time decreasing preferences for unhealthy products (38,39) . Furthermore, healthy sponsorships are likely to be mutually beneficial to business and sporting clubs (40) .…”
Section: Discussionmentioning
confidence: 99%
“…However, at present, few healthier food brands are leveraging junior sport sponsorship to strengthen their brand image (2) . Further, there are only a couple of examples in the literature of sponsorship of children's sporting activities being used to promote public health messages (25) . This missed opportunity could go some way to being remedied through the establishment and implementation of sponsorship guidelines in community sporting settings that encourage sporting organisations to pursue pro-health sponsorship options.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, this article demonstrates how social marketing techniques can be used to inform environmental conservation. Social marketing has been proven effective in many health-related areas such as alcohol reduction, smoking caseation, physical activity, and healthy eating (Fujihira, Kubacki, Ronto, Pang, & Rundle-Thiele, 2015; Kubacki, Hurley, & Rundle-Thiele, 2018; Kubacki, Rundle-Thiele, Lahtinen, & Parkinson, 2015), but it is still underutilized in the environmental discipline. Few studies can be found to demonstrate whether and how social marketing can contribute to environmental conservation (see Salazar, Mills, & Veríssimo, 2018; Wilhelm-Rechmann, Cowling, & Difford, 2014).…”
Section: Discussionmentioning
confidence: 99%